2015
DOI: 10.18052/www.scipress.com/ilcpa.43.62
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Toxic Heavy Metals in Sediment Ecosystem of Mahim Creek near Mumbai, India

Abstract: The present study was performed for the period of one year from June 2012 to May 2013 in order to understand the level of toxic heavy metals in the sediments of Mahim Creek near Mumbai. The annual average concentration of heavy metals like Pb, Cd, Cr, Zn, Cu, Ni and Hg was found to be 9.88, 2.33, 1.41, 33.31, 22.07, 32.21 and 32.06 ppm respectively. It is feared that this heavy metals accumulated in the creek sediments might affect the benthic macro invertebrates whose metabolic activities contribute to aquati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Various studies have reported the presence of mercury at different sites of Mithi River (Nagarsekar and Kakde 2014;Singare et al 2012a, b). Annual average concentration of mercury in Mithi river was reported to be 32.06 ppm (Singare et al 2015), which is much higher than the permissible limit (0.001 ppm) set by Central Pollution Control Board (CPCB) of India and World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 80%
“…Various studies have reported the presence of mercury at different sites of Mithi River (Nagarsekar and Kakde 2014;Singare et al 2012a, b). Annual average concentration of mercury in Mithi river was reported to be 32.06 ppm (Singare et al 2015), which is much higher than the permissible limit (0.001 ppm) set by Central Pollution Control Board (CPCB) of India and World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 80%